Effect of Allelochemicals from Cereal Rye Cultivar and Pythium lutarium on Corn Growth and Disease - Jyotsna Acharya; Alison E. Robertson (PhytoFrontiers, 2023)
Allelopathic chemicals produced by a cereal rye (CR; Secale cereale L.) cover crop have been implicated in the negative effect of CR on corn planted into decomposing CR residue. Production of allelochemicals varies among CR cultivars. In the current study, the allelopathic effect of crude extracts from five CR cultivars (Elbon, Hazlet, Serafino, Tayo, and Yankee) was evaluated on corn seedling growth, mycelial growth of Pythium lutarium, and root rot of corn caused by P. lutarium using a plate assay. In general, crude extracts from all CR cultivars slowed pathogen growth and reduced corn coleoptile and radicle lengths. When corn was grown on media amended with crude extracts from the CR cultivars and colonized with P. lutarium, corn growth was reduced and root rot severity increased compared with the check (no extract with pathogen). Subsequently, a cup assay was used to further investigate the allelopathic effect of Elbon, Hazlet, and Serafino on corn seedling growth and root rot. Corn grown in cups into which each cultivar had been planted had shorter radicles and coleoptiles compared with the check (no CR), regardless of the CR cultivar. Results from this study suggest that allelochemicals released from decomposing CR vary among cultivars, and their interaction with Pythium spp. could affect seedling disease on corn. Consequently, choice of CR cultivar may be an important management decision to reduce the negative effects of CR on corn. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.